The Growth of leaf cutting of malay apple (Syzygium malaccense (L.) Merr & Perry) with coconut water treatmen - Fatonah, Siti; Yani, Rama (Jurnal Pertanian, 2023)
Malay apple (Syzygium malaccense (L.) Merr & Perry) is a fruit plant in the Myrtaceae family, which has high economic value and nutritional content. The aim of this study was to determine the growth response of guava leaf cuttings to treatment with coconut water concentrations. The research design used was a randomized block design with 5 treatment levels and 5 replications. The treatment consisted of 5 levels namely control, water immersion, 25% coconut water, 50% coconut water, and 75% coconut water. Coconut water treatment was given to cuttings by soaking for 2 hours. Furthermore, leaf cuttings are planted in polybags that have been doused with water and then given a plastic cover. Parameters observed included the percentage of live cuttings, the percentage of formed roots, the percentage of shoots formed, the percentage of petiole damage, the percentage of petiole swelling and the percentage of petiole callus formation, the percentage of damaged leaves, and the symptoms of leaf damage. The results showed that the control treatment, water immersion and coconut water treatment showed the percentage of live cuttings was 100%, the leaf cuttings had not yet formed roots and shoots. Coconut water treatment reduced the percentage of petiole and leaf blade damage, increased the percentage of petiole swelling and increased callus formation, but was not able to stimulate root and shoot formation. Treatment of 75% coconut water showed the lowest percentage of damage to leaf cuttings with the highest percentage of swelling and callus formation.